ANALISIS KINERJA SISTEM INFORMASI LABORATORIUM DI RSUD KOTA SURAKARTA MENGGUNAKAN METODE IT BALANCED SCORECARD - Hanifah Wijayanti; Andriani Kusumaningrum; Sri Harjanto (STMIK Sinar Nusantara, 2019)
RSUD Surakarta has utilized information system in the hospital business process. The overall information system is managed in Sistem Informasi Manajemen Rumah Sakit (SIMRS). Information system in a laboratory called with Laboratory Information System (LIS). The use of LIS is expected to improve performance in the laboratory. For that researchers want to measure the performance of laboratory information systems to find out how far the information system provides benefits to the performance of RSUD Surakarta using IT Balanced Scorecard method. With the aim of research to analyze the achievement of the laboratory information system at RSUD Surakarta based on IT Balanced Scorecard method and to recommend what things need to be done to optimize the performance of laboratory information system. Population and sample of research is 15 laboratory staff. The result of measurement using IT Balanced Scorecard method of laboratory information system performance at RSUD Kota Surakarta is in the very good category with the average achievement of the fourth perspective is 92,92%. Four perspectives are business contribution perspective 83,34%, user orientation perspective 92,05%, operational excellence perspective 98,15%, and future orientation perspective 98,15%.Keywords: Information System, IT Balanced Scorecard, System Performance Analysis